Microwave Assisted Solvent-Free Synthesis of Novel Chenodeoxycholic Acid Thiosemicarbazone Derivatives and Studies on Antibacterial Activities - Zhao, Zhi-Gang; Yan, Ping; Liu, Xing-Li; Shi, Zhi-Chuan (Letters in Organic Chemistry, 2012)
A rapid and efficient method for the synthesis of novel chenodeoxycholicacid acid thiosemicarbzones under solvent-free conditions using microwave has been developed. Their structures were elucidated by ESI-MS, IR, 1H NMR and elemental analysis. Nine novel compounds have been synthesized in good yields. Compared to the conventional method, microwave irradiation method, main advantages are short reaction times, good conversions and the environmentally friendly nature of the process. Preliminary results showed that some of these compounds possess inhibitory effects against S. typhimurium and E. coli.
Keywords: anti-tumor